Why didn't the United States establish a central bank until after the panic of 1907? - Jon R. Moen; Ellis W. Tallman (Federal Reserve Bank of Atlanta, 1999)
Monetary historians conventionally trace the establishment of the Federal Reserve System in 1913 to the turbulence of the Panic of 1907. But why did the successful movement for creating a U.S. central bank follow the Panic of 1907 and not any earlier National Banking Era panic? The 1907 panic displayed a less severe output contraction than other national banking era panics, and national bank deposit and loan data suggest only a limited impairment to intermediation through these institutions. ; We argue that the Panic of 1907 was substantially different from earlier National Banking Era panics. The 1907 financial crisis focused on New York City trust companies, a relatively unregulated intermediary outside the control of the New York Clearinghouse. Yet trusts comprised a large proportion of New York City intermediary assets in 1907. Prior panics struck primarily national banks that were within the influence of the clearinghouses, and the private clearinghouses provided liquidity to member institutions that were perceived as solvent. Absent timely information on trusts, the New York Clearinghouse offered insufficient liquidity to the trust companies to quell the panic quickly. ; In the aftermath of the 1907 panic, New York bankers saw heightened danger to the financial system arising from "riskier" institutions outside of their clearinghouse and beyond their direct influence. The reform proposals from New York banking interests advocated universal membership in a centralized reserve system to overcome the risk of financial panic arising from the observed isolation of some intermediaries. Serious consideration of federal legislation to reform the banking system took place because New York bankers changed in their attitude toward a system of reserves beyond their control.
Keywords: 330; Banks and banking - History; Banks and banking; Central